2020
DOI: 10.1038/s41386-020-00819-0
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β inhibition restores cortical gamma oscillation and cognitive behavior in a mouse model of NMDA receptor hypofunction relevant to schizophrenia

Abstract: Cortical gamma oscillations are believed to be involved in mental processes which are disturbed in schizophrenia. For example, the magnitudes of sensory-evoked oscillations, as measured by auditory steady-state responses (ASSRs) at 40 Hz, are robustly diminished, whereas the baseline gamma power is enhanced in schizophrenia. Such dual gamma oscillation abnormalities are also present in a mouse model of N-methyl-D-aspartate receptor hypofunction (Ppp1r2cre/Grin1 knockout mice). However, it is unclear whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Similarly, treatment with BRD3731, a selective GSK-3β inhibitor, normalized abnormal cortical gamma oscillations and reversed deficits in working memory and acoustic startle of prepulse inhibition (PPI) in mice carrying a hypofunctional NMDS (N-methyl-d-aspartate) receptor (Nakao et al, 2020). In confirmation, subsequent knockdown of GSK-3β in these mice also reversed these behavioral deficits (Nakao et al, 2020).…”
Section: Schizophreniamentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, treatment with BRD3731, a selective GSK-3β inhibitor, normalized abnormal cortical gamma oscillations and reversed deficits in working memory and acoustic startle of prepulse inhibition (PPI) in mice carrying a hypofunctional NMDS (N-methyl-d-aspartate) receptor (Nakao et al, 2020). In confirmation, subsequent knockdown of GSK-3β in these mice also reversed these behavioral deficits (Nakao et al, 2020).…”
Section: Schizophreniamentioning
confidence: 85%
“…In mice carrying a microdeletion on chromosome 22q11.2, a mutation that accounts for about 1%-2% of sporadic schizophrenia (Tamura et al, 2016), treatment with SB-216763 at the postnatal stage, rescued deficits in neural synchrony, taskrelated neural activity, and spatial working memory (Tamura et al, 2016). Similarly, treatment with BRD3731, a selective GSK-3β inhibitor, normalized abnormal cortical gamma oscillations and reversed deficits in working memory and acoustic startle of prepulse inhibition (PPI) in mice carrying a hypofunctional NMDS (N-methyl-d-aspartate) receptor (Nakao et al, 2020). In confirmation, subsequent knockdown of GSK-3β in these mice also reversed these behavioral deficits (Nakao et al, 2020).…”
Section: Schizophreniamentioning
confidence: 99%
“…Additionally, Nguyen et al [ 193 ] demonstrated that the inhibition of GSK-3 in rats, by a selective inhibitor or lithium, also influenced both theta and gamma band activity. GSK-3β inhibition in the corticolimbic interneurons of Ppp1r2-cre/floxed-Grin1 knockout mice has also been shown to both ameliorate deficits in spatial working memory and evoke gamma power increases in the primary auditory cortex [ 194 ]. Importantly, evidence suggests that reductions in 5-HT signaling, the main outcome of IDO’s metabolic process, may also influence neuronal system activity.…”
Section: System-wide Effects Of Pathogenic Gsk-3 and Inflammation In Mddmentioning
confidence: 99%
“…In the search of cortical excitability, we used in vivo local field potential (LFP) recording in awake animals, and applied periodic auditory steady-state response (ASSR) stimuli, comprised of 50 repetitions of 40-Hz click-trains with inter-stimulus interval (ISI) of 20 s. As previously reported [ 19 , 20 ], the Grin1 mutant mice show diminished ASSR oscillatory power following the N1 peak (the first negatively-evoked response). Here we found that N1 -like spontaneous LFP activities were frequently observed during ISIs in the Grin1 mutant mice, suggesting cortical hyperexcitability elicited by ASSR acoustic stimuli.…”
Section: Introductionmentioning
confidence: 99%